TEKANAN KONGLOMERAT MEDIA TERHADAP OTONOMI INDIVIDUAL PARA PRAKTISI (Kasus Keberpihakan Pada Kandidat Melalui Pemberitaan TV One, ANTV dan Metro TV, Selama Masa Pencalonan Ketua Umum Partai Golkar 2009-2014) - Setiawan, Yuliyanto Budi (Universitas Semarang, 2010)
Mass media can be called as a company. If media owner want contruction of production result as his/her want, so that the out put will suitable with that contruction. Creativity from worker will be limited for they work situation under pressure, intervension and rule that bind from top management. That individual autonomy media crews who work in news departement in some television company are pressured. They have degradation in their work for the owner has agenda where the agenda is published by media. This is looked from publication Golkar Party when the party do competition of the leader party period 2009-2014. Some television company such as TV One, ANTV and MetroTV